1989
DOI: 10.3109/15563658908994420
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Poisoning (Scombroid Fish Poisoning): An Allergy-Like Intoxication

Abstract: Histamine poisoning results from the consumption of foods, typically certain types of fish and cheeses, that contain unusually high levels of histamine. Spoiled fish of the families, Scombridae and Scomberesocidae (e.g. tuna, mackerel, bonito), are commonly implicated in incidents of histamine poisoning, which leads to the common usage of the term, "scombroid fish poisoning", to describe this illness. However, certain non-scombroid fish, most notably mahi-mahi, bluefish, and sardines, when spoiled are also com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(124 citation statements)
references
References 22 publications
1
116
0
7
Order By: Relevance
“…It is also reported that histamine poisoning occurs more frequently in individuals with allergic inheritance (19,20). Our patients had no prior history of allergic diseases, their eosinophil counts were normal, and the IgE level of only case 4 was slightly high ( Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…It is also reported that histamine poisoning occurs more frequently in individuals with allergic inheritance (19,20). Our patients had no prior history of allergic diseases, their eosinophil counts were normal, and the IgE level of only case 4 was slightly high ( Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…La ingesta de un alimento con altos niveles de histamina produce una reacción pseudoalérgica, cuyos síntomas incluyen entre otros: hormigueo o picor en o alrededor de la boca y garganta, erupción cutánea en la parte superior del cuerpo, hipotensión, cefalea, mareo, prurito, náuseas, vómitos, diarrea, broncoconstricción, taquicardia y dificultad respiratoria. Estos síntomas habitualmente comienzan desde unos pocos minutos a unas pocas horas desde el consumo del alimento y duran entre unas horas y unos pocos días [4][5][6]8,[10][11][12][13][14] .…”
Section: Introductionunclassified
“…Tyramine was the most abundant BA in different types of soy sauces produced in China (Yongmei et al, 2009). Tsai et al (2007) tested biogenic amine levels in seven soybean and eleven black bean douchi (traditional chinese fermented soybean product), among which four soybean douchi products had histamine levels greater than 5 mg/100 g while, among the black bean douchi samples, four samples contained histamine at 56.3, 62.1, 80.2 and 80.8 mg/100 g, levels greater than 50 mg/100 g, a hazard action level (Taylor, 1989). However, histamine is not the only compound responsible for scombrotoxicosis (acute onset of gastrointestinal symptoms such as headache, flushing and hypertension after ingesting spoiled fish), since ingestion of pure histamine does not automatically cause toxic symptoms (Bjeldanes et al, 1978).…”
Section: Occurrence Of Biogenic Amines In Soybean Foodmentioning
confidence: 99%